Anesthetic Management of Carcinoma Breast during Third Trimester of Pregnancy: a Case Report - Gautam, Ashok; Dhakal, Yogesh; Khadka, Sarada (Journal of BP Koirala Institute of Health Sciences, 2023)
Although malignancy during pregnancy is uncommon, if occurs, it adds challenge to ensure safety of both the mother and fetus. A 36-year lady was diagnosed with carcinoma breast and scheduled for modified radical mastectomy at 29 weeks of gestation. The case was conducted under general anesthesia with intraoperative pectoralis nerve block for postoperative analgesia. Care was taken to avoid hypotension, tachycardia and hypercarbia so that the placental perfusion was not hampered. The trachea was extubated and immediate postoperative obstetrician review revealed no abnormality in the fetal heart rate and activity. Postoperative course was uneventful. Pregnancy was continued till 34 weeks of gestation when elective cesarean section was done under subarachnoid block. A healthy baby was delivered without any adverse consequences. Anesthesia during last trimester of pregnancy can be safely performed, when precautions are taken with involvement of proper teamwork, and the benefit of surgery outweighs the risk of postponing it.